PENGARUH KEPEMIMPINAN SITUASIONAL TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA KANTOR PT. NINDYA KARYA CABANG MAKASSAR) - Hartono Hartono; Nurdjanah Hamid; Ria Mardiana Yusuf (Hasanuddin Journal of Applied Business and Entrepreneurship, 2018)
The role of leadership will be important and necessary to harmonize the various needs and also to create a conducive working situation. This study aims to determine to know the influence of leadership on employee performance mediated by job satisfaction and OCB at PT Nindya Karya Makassar Branch. The type of research used in this study is quantitative approach. The quantitative approach bases the study of empirical rational principles. The quantitative approach bases the study of empirical rational principles. Therefore, before doing research the researcher must find the problem and hypothesis to be tested based on the criteria specified and the path analysis tool that is Smart PLS 2.0 to know the relation of the variable. The result of this research shows that situational leadership has a significant positive effect on employee job satisfaction, situational leadership has positive and significant effect on Organizational Citizenship Behavior of employees, while situational leadership has positive and insignificant effect on employee performance. As the mediation variable of job satisfaction has negative and insignificant effect on employee performance while Organization Citizenship Behavior has positive and significant effect on employee performance. For situational leadership mediation perspectives have no significant positive effect on employee performance mediated by job satisfaction while situational leadership has a positive and significant effect on employee performance mediated by organizational citizenship behavior. Keywords: Situational Leadership, Job Satisfaction, Organizational Citizenship Behavior, Employee Performance